The Functional Roles of the Cis-acting Elements in Bamboo mosaic virus RNA Genome - Chen, I-Hsuan; Huang, Ying-Wen; Tsai, Ching-Hsiu (Frontiers in Microbiology, 2017)
Bamboo mosaic virus (BaMV), which belongs to the genus Potexvirus in the family Alphaflexiviridae, has a single-stranded positive-sense RNA genome that is approximately 6400 nucleotides (nts) in length. Positive-sense RNA viruses can use genomic RNA as a template for translation and replication after entering a suitable host cell. Furthermore, such viral RNA is recognized by capsid protein for packaging and by viral movement protein(s) or the movement protein complex for cell-to-cell and systemic movement. Hence, viral RNA must contain signals for different functions to complete the viral infection cycle. In this review, we examine various cis-acting elements in the genome of BaMV. The highly structured 3ʹ untranslated region (UTR) of the BaMV genomic RNA plays multiple roles in the BaMV infection cycle, including targeting chloroplasts for RNA replication, providing an initiation site for the synthesis of minus-strand RNA, signaling for polyadenylation, and directing viral long-distance movement. The nt at the extreme 3ʹ end and the structure of the 3ʹ-terminus of minus-strand RNA are involved in the initiation of plus-strand genomic RNA synthesis. Both these regions have been mapped and reported to interact with the viral-encoded RNA-dependent RNA polymerase. Moreover, the sequences upstream of open reading frames (ORFs) 2, 3, and 5 are involved in regulating subgenomic RNA synthesis. The cis-acting elements that were identified in BaMV RNA are discussed and compared with those of other potexviruses.